Pengembangan Alat Eksperimen Penentuan Koefisien Gaya Gesek pada Bidang Miring Berbasis Induksi Magnet - Novi Yola Saiputri; Thoha Firdaus; Fatkhur Rohman (Pendidikan Fisika Universitas Nurul Huda, 2021)
This study aims to develop an experimental tool for determining the coefficient of kinetic friction on an inclined plane based on magnetic induction. The object of material used to find the value of the coefficient of kinetic friction is acrylic with wood, acrylic with acrylic, and acrylic with plastic. To determine the value of the coefficient of kinetic friction, a 620 g load was launched on a plane surface with an angle of 30° and a neodymium magnet with three solenoid coils was placed on an inclined plane to capture the magnetic induction wave signal displayed by Audacity as the generated time logging data. The development model in this study is the Plomp model. The first stage is preliminary research, the second stage is Design and Develop prototype. The results of this study indicate the validity value obtained from experimental tools and support systems with an average validation index of 0.86 with high validity criteria. While the results of the practicality test by the teacher obtained an average percentage of 82% with appropriate criteria, while the practicality test by students obtained a percentage of 78.33% with appropriate criteria. The percentage of relative error between acrylic and wood was 15% with a coefficient of kinetic friction 0.292, acrylic with acrylic 30% 0.208 0.208 and acrylic with plastic obtained 0.265. Based on these data, it can be concluded that the experimental tool for determining the coefficient of kinetic friction developed is valid and practical to be used as a learning media.